GAMBARAN PENGETAHUAN REMAJA TENTANG KESEHATAN REPRODUKSI DI DESA KERTAJAYA - Irawan, Erna (KEPERAWATAN, 2016)
Abstract - Adolescence is a period of transition from children to adults who marked change in the physical, emotional and psychological. Reproductive health knowledge is important for adolescents to improve health behaviors, to avoid free sex, and decrease in the number of infectious illness sex. The purpose of this study was to overview knowledge of reproductive health among adolescents. This study was a descriptive design. The research was conducted on October 20 until November 15, 2015 in the Desa Ketajaya Kabupaten Bandung Barat. The samples were selected from adolescents in that village using proposive sampling. . The samples used were 96 respondents. The instrument for measuring knowledge was valid and reliable. The descriptive analysis were used to analyze the data. Data showed that the respondents were females (57%) and males (43%). The respondents had average of age (Mean=12.3) years (SD=1.63). Results of the respondents knowledge is 11.5% less, 81.3% moderate, and 7.3%. The data showed that the teenager Yang memilki Still Few Good knowledge that Need No Further Research The interventions to improve the knowledge of the respondent review. Key words: Adolescent, Reproductive Health Abstrak - Masa remaja adalah masa peralihan dari anak-anak kedewasa yang ditandai perubahan fisik, emosi dan psikis. Pengetahuan tentang kesehatan reproduksi sangat penting bagi remaja untuk meningkatkan perilaku keshatan, menhindari sex bebas, dan penurunan jumlan infeksi menular seksual. Tujuan penelitian ini untuk menggambarkan pengetahuan remaja mengenai kesehatan reproduksi. Desain penelitian ini merupakan deskriptif kuantitatif. Penelitian ini dilaksanakan pada tanggal 20 Oktober sampai dengan 15 November 2015 di Desa Ketajaya Kabupaten Bandung Barat. Sampel dipilih menggunakan purposve sampling. Sample yang digunakan adalah 96 orang. Instrument untuk mengukur pengetahuan adalah valid dan reliable. Data menunjukan jumlah responden perempuan 57% dan laki-laki 43%. Rata-rata usia responden adalah (Mean-12.3) tahun (SD-1.63).  Hasil pengetahuan responden adalah 11.5% kurang, 81.3% sedang, dan 7.3% baik. Data menunjukan bahwa remaja yang memiliki pengetahuan baik masih sedikit sehingga untuk penelitian selanjutnya diharapkan untuk memberikan intervensi agar pengetahuan responden dapat meningkat. Kata Kunci: Kesehatan Reproduksi Remaja, Pengetahuan, Remaja,